Legal Review of the Application of Conventional Inheritance Law Provisions to Cryptocurrency Assets - Yulkarnaini Siregar (SEAN Institute, 2025)
The digitalization era has brought fundamental transformations to the financial sector, particularly with the emergence of cryptocurrency, which has experienced significant growth in Indonesia. However, the existence of cryptocurrency as a new investment asset raises legal implications that have not been anticipated by the existing legal system, especially in inheritance law, where the Civil Code was drafted during the Dutch colonial period when digital technology did not yet exist, thus creating complex problems in the inheritance of cryptocurrency, which has technical characteristics that differ from conventional assets. This study aims to examine the application of Indonesian inheritance law provisions to cryptocurrency assets, identify obstacles in the application of conventional inheritance law to digital assets, and explore the necessary adaptations. The study employs a normative legal approach with doctrinal research based on an analysis of Indonesian positive law principles through literature review. The results of the study indicate that cryptocurrency can be classified as intangible movable property based on Articles 503 and 504 of the Civil Code, but its practical application faces significant obstacles in terms of asset accessibility, which depends on private keys, difficulties in identifying and inventorying digital assets, and issues of proof of ownership. The conclusion states that while conventional inheritance law provisions can theoretically be applied to cryptocurrency, legal mechanisms require adaptation through expanded interpretation of will provisions, development of escrow systems, and updates to the Civil Code to provide adequate legal certainty.